The North American Trumpeter Swan Survey: retain or find something new? - Vrtiska, Mark P.; Dubovsky, James A.; Anderson, Michael G. (Wildfowl, 2024)
The Trumpeter Swan Cygnus buccinator is a charismatic species, important to many North Americans, and estimating demographic parameters – including abundance and distribution – is a basic requisite for the conservation and management of its populations. From 1968 to 2015, the primary population survey for Trumpeter Swans was the North American Trumpeter Swan Survey (NATSS), which was exceedingly useful for determining trends in abundance and range expansion following near-extirpation of the species in the first half of the 20th century. The NATSS also had some shortcomings, however, which limited its utility as an index of the swans’ status, and the NATSS has been suspended indefinitely. To help inform decisions as to whether the NATSS should be reinstated, or an alternative monitoring programme developed, we here review the strengths and drawbacks of the NATSS as well as those of other operational surveys and monitoring programmes. For instance, the Waterfowl Breeding Population and Habitat Survey, the Mid-Winter Waterfowl Survey, the Breeding Bird Survey, the Christmas Bird Count, and eBird data also cover large areas of the Trumpeter Swans’ range during certain (albeit different) periods of the year, and several have been mentioned as possible alternatives to the NATSS for assessing the status of Trumpeter Swan populations in North America, but each also has some limitations. We discuss the types of data that each of these monitoring efforts generate, and whether any might provide information sufficiently useful for managing Trumpeter Swan populations and their habitats effectively. We hope that this critique will not only be useful to federal, state and provincial agencies as they develop monitoring programmes for revision of management objectives, but that it will help to stimulate the development of updated strategies for Trumpeter Swan conservation.